Efficacy and Safety of Ocriplasmin Use for Vitreomacular Adhesion and Its Predictive Factors: A Systematic Review and Meta-Analysis - Chen, Xi; Li, Min; You, Ran; Wang, Wei; Wang, Yanling (Frontiers in Medicine, 2022)
Symptomatic vitreomacular adhesion (sVMA) impedes visual acuity and quality. Ocriplasmin is a recombinant protease which may be injected into the vitreous cavity to treat this condition, yet controversy remains regarding its effectiveness and safety, particularly its patient selection standard. In this systematic review, PubMed, EMBASE, and the Cochrane Library were searched to identify studies published prior to August 2020 on the impact of ocriplasmin treatment on VMA release, macular hole (MH) closure and/or related adverse events (AEs). Data were pooled using a random-effects model. Risk ratios (RR) with 95% confidence intervals (CIs) were calculated. Of 1,186 articles reviewed, 5 randomized controlled trials and 50 cohort studies were ultimately included, representing 4,159 patients. Ocriplasmin significantly increased the rate of VMA release (RR, 3.61; 95% CI, 1.99-6.53; 28 days after treatment) and MH closure (RR, 3.84; 95% CI, 1.62-9.08; 28 days after treatment), and was associated with visual function improvement. No increased risk for overall AEs was seen in ocriplasmin treatment. The proportion of VMA release and MH closure patients was 0.50 and 0.36 respectively. VMA release was more likely in patients with absence of ERM. Patients with smaller MH diameter were more likely to achieve MH closure. Evidence from included studies suggests that ocriplasmin is a suitable and safe approach for treating sVMA. ERM and MH status are important factors when considering ocriplasmin treatment.